Mutational analysis of an essential binding site for the U3 snoRNA in the 5' external transcribed spacer of yeast pre-rRNA. - Beltrame, M (Nucleic Acids Res, 1994)
The small nucleolar RNA U3 is essential for viability in yeast. We have previously shown that U3 can be cross-linked in vivo to the pre-rRNA in the 5' external transcribed spacer (ETS), at +470. This ETS region contains 10 nucleotides of perfect complementarity to U3. In a genetic background where the mutated rDNA is the only transcribed rDNA repeat, the deletion of the 10 nt complementary to U3 is lethal. Cells lacking the U3 complementary sequence in pre-rRNA fail to accumulate 18S rRNA: pre-rRNA processing is inhibited at sites A0 in the 5' ETS, A1 at the 5' end of 18S rRNA and A2 in ITS1. We show here that effects on processing at site A0 are specific for U3 and its associated proteins and are not seen on depletion of other snoRNP components. The deletion of the sequence complementary to U3 in the ETS therefore mimics all the known effects of the depletion of U3 in trans. This indicates that we have identified an essential U3 binding site on pre-rRNA, required in cis for the maturation of 18S rRNA. IMAGES: